The Use of Interactive Learning by Tutor to Develop Learning Materials in Islamic Education on The Package C Program - Ciptro Handrianto; Ahmad Jazimin Jusoh; Syuraini Syuraini; M Arinal Rahman; Ary Kiswanto Kenedi; Piki Setri Pernantah; Shahid Rasool (FITK UIN Walisongo, 2022)
The aim of this study was to investigate the use of interactive learning by tutors in developing learning materials in Islamic Education on the Package C program. The methodology used in this study was quantitative with a survey approach. There were 30 Package C learners as participants involved in this study. A set of questionnaires was distributed to participants, and data were analyzed using descriptive quantitative analysis. The study showed that the tutors used interactive learning to develop learning materials by involving the participants in arranging the learning topic. Most participants agreed about the interactive learning in the Package C program, which was shown in a high percentage of their responses. It concluded that the interactive learning approach by tutors in the Package C program was effective in developing learning materials among learners. The recommendation of the study was that the government should hugely adopt interactive learning to design and develop the Package C program so that the learners were more enthusiastic and motivated to study.